"The End of Privacy". (Quill)
The article announces that "The End of Privacy" series of articles which appeared in the newspaper "The Wall Street Journal" was named one of the winners in the Public Service Journalism category of the Society of Professional Journalists' (SPJ) 2011 Sigma Delta Chi Awards.